Multidisciplinary Management of Acute Tetraparesis in an Infant with Achondroplasia, with a Focus on Anesthetic Strategies: A Case Report - Barbora Nedomová; Robert Chrenko; Salome Jakešová; Petra Zahradníková; Martin Hanko; Ľubica Tichá (Children)
Background/Objectives: This report details a rare instance of an infant with achondroplasia developing acute tetraparesis after a cervical whiplash injury, highlighting key multidisciplinary management considerations and specific anesthetic strategies to mitigate potential risks. Case presentation: A 1-year-old boy with achondroplasia presented with acute tetraparesis after a whiplash injury. Initial craniocervical computed tomography demonstrated a reduced volume of the posterior fossa, foramen magnum stenosis, and ventriculomegaly, without any fractures or dislocations. Moreover, magnetic resonance imaging (MRI) revealed pathological signal changes in the medulla oblongata, cervical spinal cord in segments C1 and C2, and the posterior atlantoaxial ligament. After initial conservative therapy and head immobilization using a soft cervical collar, partial remission of the tetraparesis was achieved. Two weeks post-injury, microsurgical posterior fossa decompression extending to the foramen magnum and C1 laminectomy was performed under general anesthesia with intraoperative neuromonitoring. Following an unsuccessful intubation attempt using a fiberoptic bronchoscope, successful airway management was achieved using a combined technique incorporating video laryngoscopy. Venous access was secured under ultrasound guidance. The patient exhibited complete remission of neurological symptoms by the third postoperative month during follow-up. Conclusions: This case report underscores the crucial need for a multidisciplinary approach in managing children with achondroplasia, especially with foramen magnum stenosis and complex cervical spine injuries. Anesthetic management required meticulously planned airway strategies using advanced techniques like video laryngoscopy and fiberoptic bronchoscopy to reduce airway risks. It also highlights the importance of conservative therapy paired with timely neurosurgical intervention, resulting in the patient’s full recovery.